Bringing the local back in. The role of territories in the “biological” transition process toward circular economy: A perspective of analysis - Taddeo, Raffaella (Frontiers in Sustainability, 2022)
As widely evidenced in the last decades, the level of “humanity’s metabolism” is unsustainable and must be reduced. It is especially related to issues such as availability of resources, impacts of transportation, waste management and external costs, that could adversely affect the economic and environmental scenario at a global level. In the transition to Circular Economy (CE), moving from the insights of Industrial Ecology (IE) and the related “biological paradigm”, it has been suggested that the meso scale is the one in which great efficiencies can be achieved; the focus is on territories in which networks of economic actors’ express significant potential in terms of synergistic and efficient use of resources and wastes. This article aims to propose a detailed methodological viewpoint, moving from the scientific and empirical experience gained in a long-term research conducted by the author on IE, CE and their development in local contexts. The first phase of the research was characterized by theoretical-methodological in-depth analysis, case studies and pilot tests, including different operating local contexts to evaluate their potential for the development of IE-based approaches. Results obtained and the experiences gained have been used to develop an interpretative framework for assessing the role of external factors in influencing the process of development. Currently, the research is aimed at developing an analytical model capable of representing both the structural and operational characteristics of such contexts and the relative factors of influence in view of the adoption of circular strategies for the territory in which they are located.